2021
DOI: 10.3390/diagnostics11111985
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Patellofemoral Morphometry Reveals Age and Gender Variations in the Knees of Children and Adolescents

Abstract: Background: The morphology and alignment of the patellofemoral joint are crucial risk factors for patellar instability, and the incidence of acute primary patellar dislocation is the highest in women in their second decade of life. The purpose of the study was to analyze age and gender variations of the patellofemoral joint using magnetic resonance imaging (MRI). Methods: A total of 852 patients aged between 4 and 18 years with a history of knee MRI examinations were screened for eligibility and 663 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In this study, age and sex matching analysis with subsequent multivariable analysis adjusted for the patient’s height and weight were employed to maximize confounder control, as several confounding factors related to patient’s specific anatomy, such as knee size, sex and patient’s height were previously found to be associated with alteration of TT–TG measurements [7, 19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, age and sex matching analysis with subsequent multivariable analysis adjusted for the patient’s height and weight were employed to maximize confounder control, as several confounding factors related to patient’s specific anatomy, such as knee size, sex and patient’s height were previously found to be associated with alteration of TT–TG measurements [7, 19].…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, the ratio of males and females with patellar dislocation varies, 64.5% females and 35.5% males were recorded in this study, which was consistent with previous studies, that females are more prone in patellar dislocation. 6,35 Among those patients, 56% of them were suffering RPD while 44% were suffering FPD. Previous studies have reported that after RPD, it may occur again in more than 50% of patients with FPD.…”
Section: The Characteristics and Distribution Of Patellar Dislocationmentioning
confidence: 99%
“…B-D), 38 and the depth of the femoral trochlea become shallower and the groove angle showed an increase with age in females, which was also the reason why females had more patellar instability than males before adolescence. 35,39 We conducted statistics on the activities of patients with patellar dislocation, and found that more than half of the patients suffering patellar dislocation partly because of sports accidents, followed by life accidents such as squatting or going down stairs. Higher intensity exercise, especially basketball, football, and table tennis, account for the most causes of patellar dislocation as reported by Höhne et al 40 In terms of age group, the majority of patients with patellar dislocation were adolescents, followed by young adults, this was consistent with the results of the study by Hasler.…”
Section: Figurementioning
confidence: 99%
“…talus dysplasia. [2][3][4][5] Epidemiological surveys have found that the incidence of patellar dislocation can be as high as 43/100,000 and is mostly associated with young women. [6,7] The clinical symptoms are mainly pain (aggravated by going up and down stairs, squatting), instability (weakness, limpness), knee strangulation, recurrent swelling and movement disorders (afraid to run and jump or easily fall down).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Prevalent in obese adolescent females, this population frequently includes congenital pathological changes such as high patella, increased anterior femoral inclination, and femoral talus dysplasia. [2–5] Epidemiological surveys have found that the incidence of patellar dislocation can be as high as 43/100,000 and is mostly associated with young women. [6,7] The clinical symptoms are mainly pain (aggravated by going up and down stairs, squatting), instability (weakness, limpness), knee strangulation, recurrent swelling and movement disorders (afraid to run and jump or easily fall down).…”
Section: Introductionmentioning
confidence: 99%